Unravelling the Cavity-Nesting Network at Large Spatial Scales: The Biogeographic Role of Woodpeckers as Ecosystem Engineers - Vergara-Egert, P; Quiroz-Espinoza, M; Fierro-Tapia, C; Moreira-Arce, D; Alaniz-Baeza, A; Carvajal-Leon, M; Hidalgo-Corrotea, C (John Wiley and Sons Inc, 2024)
Aim: Primary cavity nesters (e.g. woodpeckers) act as ecosystem engineers by providing tree cavities to several vertebrates that use them as nests or refuges. Although diverse assemblages of primary excavators are assumed to increase the number of tree cavities, environmental factors can limit populations of primary excavators, thus weakening their ecological function. We aim to test the biogeographical-scale relationships between primary excavators and cavity users by distinguishing the contribution of environmental variables. Location: Southern South America. Materials and Methods: We used species distribution models, which combine bioclimatic and remote sensing derived variables, to map the richness of vertebrates composing the cavity-network of temperate and Mediterranean forests of South America. Based on a resampling procedure for ensuring spatial independence, we fitted structural equation models to estimate relationships between forest characteristics and cavity user vertebrates. Results: Richness of secondary cavity users (mammals, obligated, habitat generalists and forest specialists) were positively and strongly influenced by the richness of primary excavators. Environmental variables affected differently the richness of primary and secondary cavity users. The richness of primary cavity users responded to tree richness and height while that of habitat specialist secondary users was positively affected by primary productivity and negatively by sclerophyll forests. Main Conclusions: Our results confirm the role of primary excavators as ecosystem engineers but highlight the importance of considering large spatial scales when analysing cavity-nesting networks. Biogeographical patterns of tree diversity and forest structure can be important drivers of cavity nesting networks that remain hidden when studies are conducted over fine spatial scales. © 2023 John Wiley & Sons Ltd.